Molecular diagnostics of hereditary medullary thyroid carcinoma - Ziemnicka, Katarzyna; Kaczmarek, Marta; Hoppe-Gołębiewska, Justyna; Słomski, Ryszard; Słowiński, Jerzy (Contemporary Oncology/Współczesna Onkologia, 2005)
Genetic studies of the RET proto-oncogene (which encodes a receptor tyrosine kinase) conducted in patients with medullary thyroid carcinoma enable early diagnosis and prophylactic treatment in members of the family being carriers of the mutation. Described autosomal dominant mutations are localized within exons: 10, 11, 13, 14, 15 and 16 of this gene and in the majority of cases affect a conservative region rich in cystein residues. Recently published data indicated a correlation between the genotype and a specific phenotype that is presence of isolated medullary thyroid carcinoma and coexistence of other disorders like pheochromocytoma or parathyroid gland adenoma (MEN 2 syndromes). In medullary thyroid carcinoma the RET proto-oncogene mutations lead to the activation of the receptor localized within the cell membrane that in consequence leads to the increased synthesis of proteins taking part among others in the proliferation of the cells, whereas mutations leading to the loss of receptor function appears in Hirschsprung’s disease (colon aganglionosis). The most common genetic defects in the medullary thyroid carcinoma are point mutations within codon 634 of exon 11 of the RET proto-oncogene. Due to the possibility of early neoplasmatic transformation it is recommended to perform prophylactic thyroidectomy in the mutation carrier, and the age of surgery is strongly connected with the site of mutation. This publication reviews elementary information about the role of RET and genetic defects of its gene leading to the development of medullary thyroid carcinoma.